Kemauan Membayar (WTP) Konsumen terhadap Jeruk Mandarin dan Jeruk Siam di Provinsi DKI Jakarta beserta Faktor-faktor yang Memengaruhinya - Hamdani, Fauzan; Suprabowo, Rizky Lutfi; Ramadwika, Risman; Fitriadi, Mochammad Yunus Gerry (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
ABSTRACTOne of Indonesia's leading horticultural commodities is oranges, with siam oranges dominating domestic production. However, many Indonesian consumers also prefer imported oranges, particularly mandarin oranges from China. The purpose of this study is to analyze consumers' Willingness to Pay (WTP) for mandarin and siam oranges, as well as to identify the factors influencing it in DKI Jakarta Province. The Contingent Valuation Method (CVM) was employed through consumer surveys to determine the price consumers are willing to pay based on the quality attributes of oranges. The research findings show that 80% of respondents are willing to pay above the market price for both Siam and Mandarin oranges. The average WTP for Siam oranges is IDR 22,480/kg, which is higher than the market price of IDR 18,000/kg. Meanwhile, the average WTP for Mandarin oranges is IDR 39,985/kg, exceeding the market price of IDR 37,000/kg. Factors that significantly influence the WTP for both Siam and Mandarin oranges include the frequency of fruit consumption, income level, and number of family members. For Mandarin oranges specifically, the significant influencing factors are income level and price. These findings indicate that consumers in the Special Capital Region of Jakarta have a stronger preference for Mandarin oranges compared to Siam oranges. Therefore, better marketing and distribution strategies are needed to enhance the competitiveness of Siam oranges against imported products. Additionally, improving quality and providing information about the health benefits of local oranges may encourage an increase in consumers' WTP for domestically produced oranges.